Reduced Competition Effects and Noisier Representations in a Second Language. Issue 1 (14th August 2019) - Tachihara, Karina; Goldberg, Adele E.
Abstract : Native speakers strongly disprefer novel formulations when a conventional alternative expresses the same intended message, presumably because the more conventional form competes with the novel form. In five studies, second language (L2) speakers were less influenced by competing alternatives than native speakers. L2 speakers accepted novel interpretable sentences more readily than native speakers, and were somewhat less likely to offer competing alternatives as paraphrases or to prefer competing alternatives in forced‐choice tasks. They were unaffected by exposure to competing alternatives immediately before judgments. Reduced sensitivity to competing alternatives was confirmed by L2 speakers' greater divergence from native speakers on judgments for novel formulations compared to familiar ones. Reduced sensitivity to competing alternatives also predicts noisier linguistic representations; consistent with this, L2 speakers performed worse on a verbatim recognition task, with performance correlating with more nativelike judgments. Proficiency was a modest predictor of judgments, but transfer effects were not. Open Practices: This article has been awarded a Preregistered Research Design badge. Preregistration for this study's research design and analyses is publicly accessible through AsPredicted.org. Direct links to the five preregistered experiments are available in the Supporting Information file. Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :